Quand l’impensable guide l’intervention. L’imprévisible accident mortel dans l’activité des agents de contrôle du travail - Emmanuelle Reille-Baudrin; Christiane Werthe (Activités)
The purpose of this article was to define what intervening means, on the basis of unexpected developments during an intervention on mental health requested by a Department of Work in France.From the order to act through to the intervention, we examined use of the “instruction to the double” method, allowing us to analyze this intervention as a “sifting process” of ordinary work activity. This collective process made death thinkable and thus a subject for debate for the team. We analysed the clinical conditions implemented to support a positive framework for professionals: from morbid and individual accounts of the tragedy to collective objectification of a work practice in order to face up to the ever possible occurrence of a work accident.We showed how the different steps of the intervention contribute to the affect civilization process in the unpredictable event of a mortal accident during the activity of work control agents.